A tactile sensing capsule endoscope employing force sensing cantilevers for tumor diagnosis in the GI tract - Peker, Furkan; Akcan, O. Gokalp; Atak, Dila; Ozata, Ibrahim H.; Uymaz, Derya S.; Balik, Emre; Ferhanoglu, Onur (Elsevier Science Sa, 2026)
The correlation between tissue elasticity and histopathological diagnosis has brought attention to the develop ment of biomedical devices for in-vivo measurement of tissue biomechanical properties. Towards this aim, we have developed a tactile sensing capsule endoscope to measure tissue Young's modulus, in situ. Inspired by force microscopy, the capsule comprises four cantilevers that probe the walls of the GI tract using a single miniaturized actuator. The force exerted on the cantilever tip by the tissue is measured using the piezoelectric layer integrated on the cantilevers. The tactile-based modulus sensing capsule was initially tested on ex-vivo animal tissue, fol lowed by healthy and cancerous human specimens. The results clearly delineate the differences in mechanical properties, with a Young's modulus of 11.3 +/- 2.3 kPa for healthy and 26.8 +/- 4.6 kPa for cancerous tissue. Overall, in the realm of tactile-based modulus sensing of tissues, our technology uniquely combines localized, quantitative Young's modulus measurements with the capability to perform multiple measurements throughout the GI tract wall in a single procedure. Moreover, the developed sensor has a compact form factor, in accordance with the capsule dimensions, and simple manufacturing steps using stereolithography. With further improvements, the developed medical device can be utilized as a non-invasive diagnostic tool in the clinic.
Keywords: Biomechanical Measurements; Capsule Endoscopy; Tactile Sensing; Early Cancer Diagnosis